Magnetoencephalography in Preoperative Epileptic Foci Localization: Enlightenment from Cognitive Studies - Wang, Qian; Teng, Pengfei; Luan, Guoming (Frontiers in Computational Neuroscience, 2017)
Over 30% epileptic patients are refractory to medication, who are amenable to neurosurgical treatment. Non-invasive brain imaging technologies including video-electroencephalogram (EEG), magnetic resonance imaging (MRI), and magnetoencephalography (MEG) are widely used in presurgical assessment of epileptic patients. This review mainly discussed the current development of clinical MEG imaging as a diagnose approach, and its correlations with the golden standard intracranial electroencephalogram (iEEG). More importantly, this review discussed the possible applications of functional networks in preoperative epileptic foci localization in future studies.